A Content Analysis of Compatible Fit among Message Elements in Philanthropy Ads. (2nd November 2018) - Hong, Ji Mi; Lee, Wei-Na; ,
ABSTRACT: This research examined philanthropy ad messages in terms of four key elements: philanthropy goal, beneficiary, expected fundraising impact, and how the suggested donation is appraised. A content analysis was carried out to systematically study ad messages from nonprofit organizations on the Philanthropy 400 list. Specifically, the frequency of appearance of each type of message elements was analyzed in terms of four theoretical concepts: regulatory focus (promotion vs. prevention goal), egoism/altruism (self vs. others as beneficiary), temporal orientation (present vs. future fundraising impact), and efficacy appraisal (self- vs. response-efficacy in how a donation is appraised). Since past research further suggests that persuasion may be enhanced when message elements are well matched in terms of "compatible fits, " this study further analyzed how the four message elements were combined in usage. The findings of this research show that while most nonprofit organizations actively utilized all four types of elements in their messages, the current practice did not follow the guidelines as would be suggested by compatible fits literature. In this respect, more research is needed to understand the discrepancy and provide better guidelines for future communication strategies in the nonprofit sector.